Auditor Style and Common Disclosure Issues: Evidence from SEC Comment Letters - Baugh, Matthew D.; Schmardebeck, Roy (The Accounting Review, 2023)
ABSTRACT Policies and procedures that centralize decision making within an audit firm create auditor style effects. Prior research suggests this style increases financial-statement comparability, implicitly making financial statements more useful. However, a potential hazard of auditor style is the propagation of decision errors. We examine the association between auditor style and common disclosure issues among audit clients. We measure auditor style as the presence of a common auditor and use comments given in the Securities and Exchange Commission’s (SEC’s) filing-review process to measure the occurrence of common disclosure issues. We find that auditor style is associated with common disclosure issues among Big 4 clientele. We also find that clients with the same auditor converge in issues as tenure increases and some evidence that clients assume the issues of a subsequent auditor. These results provide the first evidence that auditor style has potential costs in the form of common disclosure issues. Data Availability: All data are publicly available. JEL Classifications: M41; M42.